Relationship between small for gestational age and aortic intima-media thickness in newborns - Ahmad Bayu Alfarizi; Ria Nova; Julniar Mawardi Tasli; Theodorus Theodorus (Indonesian Pediatric Society, 2014)
Background Small for gestational age (SGA) has been associatedwith adult cardiovascular disease. Small for gestational agenewborns may undergo early aortic wall intima-media thickening(aIMT) in utero.Objective To determine the relationship between SGA as a riskfactor for increased aIMT, as a sign of atherosclerosis onset.Methods We conducted a case-control study in the Neonatal Wardand Rooming-in Nursery at Dr. Mohammad Hoesin Hospital,Palembang, between April to June 2012. Subjects were allocatedto either the case group (aIMT 2: 0.9 mm) or to the controlgroup (aIMT <0.9 mm). Newborns were classified as SGA iftheir birthweight (BW) was < l O'h percentile, and appropriatefor gestational age (AGA) if their BW was between lQth - 90'hpercentile, according to the Lubchenco curve. Abdominal aorticintima-media thickness was measured by echocardiographyexamination.Results The case and control groups consisted of 30 n ewbornseach. The proportion of SGA newborns was higher in the casegroup than the control group. The likelihood of infants in the casegroup being SGA was significantly higher compared to the controlgroup, with odds ratio of 10.8 (95%CI 3,26 to 35, 72) . The meanaIMT was significantly higher in SGA than in AGA infants, 0.9(SD 0.16) mm vs. 0.8 (SD 0.13) mm, respectively, with a meandifference of 0, 13 (9 5% CI 0, 050 to 0,209 mm; P